Masking exposure to phobic stimuli reduces fear without inducing electrodermal activity. (11th December 2017) - Siegel, Paul; Warren, Richard; Jacobson, Gabriella; Merritt, Edward
Abstract: A series of experiments has shown that limiting awareness of exposure to feared stimuli through visual masking—or very brief exposure (VBE)—reduces avoidance of a live tarantula by spider‐phobic participants. We investigated this process of fear reduction by directly relating the effects of VBE on electrodermal activity to its ensuing effects on phobic behavior. Sixty spider‐phobic participants, identified by approaching a live tarantula and a questionnaire, were administered either VBE to masked spiders or control exposure to masked flowers. Skin conductance levels (SCLs) were continuously recorded during exposure. The participants approached the tarantula again immediately thereafter. VBE reduced avoidance of the tarantula and did not increase SCLs or cause subjective distress relative to control exposure. SCL increases during VBE were strongly negatively correlated with the reduction of self‐reported fear of the tarantula: the less that SCLs increased during VBE, the more it reduced fear. VBE only increased SCLs in participants whose fear was not reduced; it did not increase SCLs in participants whose fear of the tarantula was reduced. Awareness of the stimuli did not mediate these effects. Control exposure did not yield any of these effects. In a second experiment, clearly visible exposure to spider images increased SCLs and subjective distress more than both VBE and control exposure, whereas VBE did not increase SCLs or subjective distress relative to control exposure within the same spider‐phobic participants. These findings suggest that exposure to phobic images can reduce fear even when it bypasses the induction of electrodermal activity.